Outcomes and challenges of an international convention centre's local procurement strategy. (December 2019) - Harrison, Bronwen; Foley, Carmel; Edwards, Deborah; Donaghy, Geoff
Abstract: Opportunities exist for organisations in urban environments to adopt strategies to support struggling rural communities. In the food sector, organisations can engage small local suppliers via a targeted short food supply chain procurement program. We report on an Australian case study in which a large international convention centre has committed to support small local suppliers by engaging them to provide their fresh produce requirements. This article contributes to the literature on the benefits and challenges of a short food supply chain approach to procurement. We argue that despite an incongruent and novel relationship between a large consumer and small local suppliers that there are several reasons to encourage such a collaboration including reduction of market volatility, increased direct expenditure, employment opportunities, and improved environmental sustainability practices. We identify potential opportunities and issues for both parties to consider in relation to risk, collaboration and trust. Highlights: Large organisation engages small regional producers in a targeted SFSC procurement program. Engaging local producers provides economic development benefits for individual suppliers and regional benefits too. SFSC programs support local producers, aligns with government strategies, and reduces food miles and carbon footprint. Small producers are exposed to challenges related to efficient logistics, developing trust and managing risk.